The influence of oxalate on renal epithelial and interstitial cells - Knoll, Thomas; Steidler, Annette; Trojan, Lutz; Sagi, Sreedhar; Schaaf, Axel; Yard, Benito A.; Michel, Maurice Stephan; Alken, Peter (Urological research, 2004)
Most renal stones in humans are composed of calcium oxalate. An increase in urinary oxalate levels has been shown to result in renal epithelial cell injury and crystal retention. However, the underlying mechanisms are unclear. Although the localization of primary stone formation and the associated cells playing the pivotal role in stone formation are still unknown, renal epithelial cells and interstitial cells seem to be involved in this process. The aim of this study was to evaluate the effects of oxalate on distinct renal epithelial and endothelial cells as well as fibroblasts. The first part focused on the toxicity of oxalate on the cells and a potential time- and dose-dependency. In the second part, renal epithelial cells were cultured in a two-compartment model to examine the vulnerability of the tubular or basolateral side to oxalate. LLCPK1, MDCK, renal fibroblast and endothelial cell lines were cultured under standard conditions. In part 1, cells were grown in standard culture flasks until confluent layers were achieved. Sodium oxalate was delivered at final concentrations of 1, 2 and 4 mM to either the apical or basolateral side (plain medium was delivered to the contralateral side). Cell survival was assessed microscopically by trypan blue staining after 1, 2 and 4 h. The influence of oxalate on proliferation and apoptosis induction was also investigated. In the second part, MDCK and LLCPK1 cells were grown in 6-well plates until confluent layers were achieved. Sodium oxalate at the above concentrations was applied, to either the apical or basolateral side and plain medium was delivered to the opposite side. The same protocol was then followed as in part 1. Part 1: sodium oxalate led to a time- and concentration-dependent decline in cell survival that was comparable in LLCPK1 and MDCK. Non-tubular cell lines like fibroblasts and endothelial cells were significantly more vulnerable to oxalate. These observations were reflected by significant impairment to cell proliferation. We could not demonstrate an induction of apoptosis in any cell line. Part 2: both cell lines were more vulnerable to oxalate on the basolateral side. This effect was more pronounced in MDCK cells at high oxalate concentrations (4 mM). Cells are apparently more resistant on the apical (tubular) side. Our results show that sodium oxalate has a negative effect on the growth and survival of renal epithelial cells and, to a greater extent, also fibroblasts and endothelial cells. We could not demonstrate any induction of apoptotic processes which implies a direct induction of cell necrosis. The finding of interstitial calcification and the proximity of tubules, vessels and interstitial cells make involvement of non-tubular renal cells in tissue calcification processes possible. Renal epithelial cells are apparently more vulnerable to oxalate on their basolateral side. Therefore, calcification processes within the interstitium may exert pronounced toxic effects to these cells, leading to inflammation and necrosis. These observations further support the idea of the interstitium as a site of primary stone formation.